Colour palettes in US film trailers: a comparative analysis of movie barcode - Redfern, Nick (Umanistica Digitale, 2021)
This article analyses the smoothed movie barcodes of 173 trailers nominated for a Golden Trailer award between 2016 and 2019 across nine genres: action, animation/family, comedy, documentary, drama, fantasy/adventure, horror, romance, and thriller. The results show that colours in the nine genres are similar, dominated by dark, unsaturated colours in the orange (hue = 30° ± 30°) and azure (hue = 210° ± 30°) regions of the HSL colour wheel. Colour palettes for each genre have similar colours but show some differences in the diversity and evenness of the distributions of these colours.